The Kinetoplastid-Specific Protein TcCAL1 Plays Different Roles During In Vitro Differentiation and Host-Cell Invasion in Trypanosoma cruzi - Rodríguez-Durán, Jessica; Gallardo, Juan Pablo; Alba Soto, Catalina Dirney; Gómez, Karina Andrea; Potenza, Mariana (Frontiers in Cellular and Infection Microbiology, 2022)
In the pathogen Typanosoma cruzi, the calcium ion (Ca2+) regulates key processes for parasite survival. However, the mechanisms decoding Ca2+ signals are not fully identified or understood. Here, we investigate the role of a hypothetical Ca2+-binding protein named TcCAL1 in the in vitro life cycle of T. cruzi. Results showed that the overexpression of TcCAL1 fused to a 6X histidine tag (TcCAL1-6xHis) impaired the differentiation of epimastigotes into metacyclic trypomastigotes, significantly decreasing metacyclogenesis rates. When the virulence of transgenic metacyclic trypomastigotes was explored in mammalian cell invasion assays, we found that the percentage of infection was significantly higher in Vero cells incubated with TcCAL1-6xHis-overexpressing parasites than in controls, as well as the number of intracellular amastigotes. Additionally, the percentage of Vero cells with adhered metacyclic trypomastigotes significantly increased in samples incubated with TcCAL1-6xHis-overexpressing parasites compared with controls. In contrast, the differentiation rates from metacyclic trypomastigotes to axenic amastigotes or the epimastigote proliferation in the exponential phase of growth have not been affected by TcCAL1-6xHis overexpression. Based on our findings, we speculate that TcCAL1 exerts its function by sequestering intracellular Ca2+ by its EF-hand motifs (impairing metacyclogenesis) and/or due to an unknown activity which could be amplified by the ion binding (promoting cell invasion). This work underpins the importance of studying the kinetoplastid-specific proteins with unknown functions in pathogen parasites.